Status of polychaete (Annelida) taxonomy in Indonesia, including a checklist of Indonesian species - Pamungkas, Joko; Glasby, Christopher J. (Raffles Bulletin of Zoology, 2019)
Despite some past remarkable marine expeditions in the seas surrounding the Indo-Malay Archipelago, a checklist of Indonesian polychaete species has never been published to date. In this paper, an inventory of species was created based mainly on existing published literature. All records of Indonesian polychaetes were mapped, and this indicated a preponderance of deep-sea records in the Wallacea region, which were primarily collected by the Dutch Siboga Expedition at the turn of the 19th century. Most biodiversity studies on the fauna by local scientists have been ecological in nature and conducted in shallow water. Many specimens were not identified to species level and not vouchered in a recognised institution. Since the mid 1700s, 580 valid polychaete species (51 families) have been identified by 37 first authors in 90 taxonomic publications. Of these species, 301 species (40 families) were new to science and mostly described by R. Horst and M. Caullery. An additional 133 polychaete species and four polychaete families are also known from the species records of the Global Biodiversity Information Facility and the Ocean Biogeographic Information System. Altogether, there have been 713 polychaete species (55 families) identified from Indonesian waters. We examined the three largest polychaete repositories in Indonesia – the Museum Zoologicum Bogoriense in Bogor, Research Center for Deep Sea in Ambon, and Research Center for Oceanography in Jakarta – and found that the collections at each institution were mostly unidentified, unpublished, and not databased, suggesting that the taxonomic study of the polychaete fauna, at least locally, has been largely overlooked. Despite some challenges, international collaborative research may be the solution to improve the knowledge of the polychaete fauna of this species-rich, yet poorly known geographic region
World Polychaeta Database (WPolyD).